Effects of the essential oil from Citrus aurantium L. in experimental anxiety models in mice - Pultrini, ADM; Galindo, L. A.; Costa, M. (Elsevier B.V., 2006)
Citrus aurantium L. is popularly used to treat anxiety, among other indications suggesting central nervous system action. Previous studies showed anxiolytic effect in the essential oil from peel in mice evaluated on the elevated plus maze [Carvalho-Freitas, M.I.R., Costa, M., 2002. Anxiolytic and sedative effects of extracts and essential oil from Citrus aurantium L. Biological and Pharmaceutical Bulletin 25, 1629-1633.]. In order to better characterize the activity of the essential oil, it was evaluated in two other experimental models: the light-dark box and the marble-burying test, respectively related to generalized anxiety disorder and to obsessive compulsive disorder. Mice were treated acutely by oral route 30 min (single dose) or once a day for 15 days (repeated doses) before experimental procedures. In light-dark box test, single treatment with essential oil augmented the time spent by mice in the light chamber and the number of transitions between the two compartments. There were no observed alterations in the parameters evaluated in light-dark box after repeated treatment. Otherwise, single and repeated treatments with essential oil were able to suppress marble-burying behavior. At effective doses in the behavioral tests, mice showed no impairment on rotarod procedure after both single and repeated treatments with essential oil, denoting absence of motor deficit. Results observed in marble-burying test, related to obsessive compulsive disorder, appear more consistent than those observed in light-dark box. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Citrus aurantium; anxiety; black and white box; marble-burying test; rotarod test; mice